Association between tomographic appendicular diameter and the pathological diagnosis of acute appendicitis in the Central Military Hospital between 2015-2019 - Basaldúa-Chincha, Diego (2020)
Objective: to identify the association that exists between tomographic appendicular diameter and pathological diagnosis in patients with clinical suspicion of acute appendicitis from the Central Military Hospital from 2015 to 2019 and determine the diagnostic validity. Materials and methods: a cross-sectional analytical study was conducted. The sample was 104 postappendectomized patients from the Central Military Hospital from 2015 to 2019, who had a tomographic report due to clinical suspicion of acute appendicitis and anatomopathological analysis of the operative part. Frequency tables, a bivariate analysis (Fisher's test), prevalence ratios (PR) were estimated using Poisson regression and diagnostic validity tests for each of the tomographic criteria were made. Results: of 104 patients, 35% were 18 to 30 years old, 69% were male; 86 patients were confirmed by pathology; of which, 70 of them presented appendicular diameter ≥ 6 mm. It was observed that the appendicular diameter, the wall thickness, the alteration of the periapendicular fat and the free fluid had statistically significant differences in relation to the pathological result. The appendicular diameter had a sensitivity of 81.4%, specificity of 55.5%, positive predictive value of 89.7% and negative predictive value of 38.4%. Conclusions: an appendicular diameter ≥ 6 mm is associated with a probability of 1.45 times that the pathological result is positive in patients with clinical suspicion of acute appendicitis.